Patterns of ambulatory dispersal in Tetranychus urticae can be associated with host plant specialization - Aguilar-Fenollosa, Ernestina; Rey-Caballero, J.; Blasco, José M.; Segarra-Moragues, J. G.; Hurtado-Ruiz, Mónica A.; Jaques, Josep A. (2017)
Dispersal can be an essential factor affecting the biological control of pests. Tetranychus urticae Koch (Acari: Tetranychidae) is a cosmopolitan and polyphagous species that may reach the pest status in many cropping systems including clementine orchards, where it may be found both in the trees and the associated flora. In a previous study, we demonstrated that the use of a ground cover of Festuca arundinacea Schreber (Poaceae) offered a better regulation of T. urticae populations than traditional alternatives (bare soil, multifloral wild cover). Therefore, we decided to study the ambulatory dispersal of mites crawling up and down tree trunks in a clementine mandarin orchard grown in association with a F. arundinacea cover for one season. The highest ambulatory migration rate was upward from the cover to the canopy. Multivariate regressions showed that the dynamics of T. urticae populations in the trees was strongly related to that of Phytoseiidae mites, their main natural predators. Surprisingly, canopy populations were not related to those on the ground cover or to those dispersing from it. When T. urticae individuals collected from the ground cover, the tree trunk, and the canopy were subjected to molecular analyses, the optimal number of genetic clusters (demes) was two. One cluster grouped individuals dispersed from the ground cover (e.g. collected on tree trunks) and 27.5 % of individuals collected in the ground cover. The second cluster grouped all the individuals collected from trees and 72.5 % of those collected in the cover. Interestingly, none of the individuals collected from the tree canopies was grouped with the first deme. This result may be taken as indicative that grass-adapted T. urticae individuals are unable to satisfactorily colonize and establish on the trees and provides evidence that host adaptation can hamper dispersal and establishment of the ground cover deme on trees, contributing to a better natural regulation of this pest species in citrus.